Análisis de prácticas emprendedoras. Estudio de caso Institución Educativa San Agustín (Memorias Sifored - Encuentros Educación UAN, 2023)
In Colombia, guidelines have been directed to promote the culture of entrepreneurship in all educational levels of the country since the promulgation of Law 1014 of 2006. However, the results are not very encouraging compared to the measurement of its impact and applicability of the rule; This is why it is necessary to study the behavior of educational institutions regarding this issue. This research was carried out under a mixed methodology, of a descriptive type, being a case study. The partial results made it possible to identify various approaches and methodologies to promote results in entrepreneurial education, in addition to recognizing the plans and actions that this institution has carried out in terms of entrepreneurship. Knowing that although a planning and projection of resources is carried out, where specific classroom projects and entrepreneurship projects are carried out in coordination with the environment, it is necessary to strengthen the supervision of activities, the evaluation of scopes and the fulfillment of planning, in addition to including in the Institutional Educational Project, spaces and specific themes related to entrepreneurship.
Keywords: curriculum renewal; education; pedagogy; skill; youth